Evaporation of single moving liquid nitrogen droplet: Experimental study and numerical simulation. (February 2023) - Cen, Kang; Li, Yiming; Wei, Lie; Li, Wenxuan; Wang, Yixi; Dai, Minxue
Highlights: A visualized experimental setup was established to investigate the dynamic evaporation characteristics of single moving LN2 droplet. Six typical gas-phase evaporation models are integrated into an in-house program so as to evaluate their accuracy and applicability for the droplet with a high evaporation rate. A novel gas-phase model is proposed for the evaporation of single moving LN2 droplet. The effects of key droplet parameters in real LN2 spray on dynamic evaporation characteristics are investigated using the new gas-phase model. Abstract: Liquid nitrogen (LN2 ) spray is composed of numerous LN2 droplets. Understanding the spray evaporation process requires firstly studying the evaporation mechanism of single moving LN2 droplet. This study focuses on experimental study and numerical simulation for evaporation characteristics of single moving LN2 droplet. A visualized experimental setup was established to investigate the dynamic evaporation characteristics of single moving LN2 droplet. The temporal evolution of LN2 droplet diameter and traveling distance was measured. The mass, energy and momentum equations between the droplet and the surrounding gases, as well as their coupled solving algorithm, are also developed to predict the temporal diameter, temperature and velocity of single moving droplet. Six typical gas-phase evaporation models are integrated into an in-house program so as to evaluate their accuracy and applicability for the droplet with a high evaporation rate. The results show that all of the six models underestimate the evaporation rate of single moving LN2 droplet. It is suggested that the Stefan blowing effect should not be taken into consideration for single moving LN2 droplet. A novel gas-phase model is then proposed for the evaporation of single moving LN2 droplet. The model can accurately predict the evaporation rate of single moving LN2 droplet when the relative velocity of LN2 is greater than 0.5 m/s, and the prediction error is within 1.1%. Furthermore, the model is also used to investigate the effects of key droplet parameters in real LN2 spray, including the initial diameter, the initial velocity, the ambient temperature and the mass fraction of nitrogen in the ambient gases, on the evaporation of single moving droplet.